Impact of prior anthracycline or taxane use on eribulin effectiveness as first-line treatment for metastatic breast cancer: results from two phase 2, multicenter, single-arm studies - O’Shaughnessy, Joyce (Springerplus, 2015)
Eribulin mesylate has efficacy in patients who have received ≥2 prior chemotherapies for metastatic breast cancer (MBC) including an anthracycline and taxane. Phase 2 trials showed clinical activity and acceptable tolerability of first-line eribulin (HER2− MBC; Study 206) and eribulin plus trastuzumab (HER2+ MBC; Study 208). Prespecified analyses evaluated efficacy by prior anthracycline and/or taxane use. Patients received eribulin mesylate (1.4 mg/m(2) IV; Days 1 and 8) and, in Study 208, trastuzumab (8 mg/kg IV/Cycle 1, then 6 mg/kg; Day 1) in 21-day cycles. Endpoints included objective response rate (ORR), progression-free survival (PFS), and tolerability. In Study 206 (N = 56), 48 % of patients had received prior anthracycline, 46 % prior taxane, 36 % prior anthracycline and taxane, and 41 % were chemotherapy-naïve. In Study 208 (N = 52), these percentages were 21, 44, 17, and 52 %, respectively. In Study 206, ORR and median PFS were similar for anthracycline-pretreated (25.9 %, 5.8 months), taxane-pretreated (26.9 %, 5.8 months), anthracycline- and taxane-pretreated (25.0 %, 6.7 months), and anthracycline/taxane-naïve patients (30.4 %, 7.6 months). In Study 208, ORR/median PFS were 63.6 %/6.7 months among anthracycline-pretreated patients, 56.5 %/6.8 months among taxane-pretreated patients, 55.6 %/5.9 months among anthracycline- and taxane-pretreated patients, and 81.5 %/13.1 months among anthracycline/taxane-naïve patients. Tolerability was generally similar among subgroups. In these studies, first-line eribulin in HER2− MBC and eribulin/trastuzumab in HER2+ MBC was effective with acceptable tolerability, regardless of prior anthracycline/taxane treatment. Prior chemotherapy was associated with lower ORR and shorter PFS with eribulin/trastuzumab in HER2+ MBC but not with eribulin in HER2− MBC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-015-1322-y) contains supplementary material, which is available to authorized users.